Philippine medical thesaurus on anatomy animal structures - Palmera, Ivy Kristina C.; Faderon, Rosalie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
The University of the Philippines College of Medicine-Philippine General Hospital (UPCM-PGH) is one of the institutions that expressed the need to organize their information resources. Consequently, a construction of a controlled vocabulary was needed to serve as supplement reference and guide material in the field of medicine. This research focused on animal structures subcategory of the 17 subcategories of 'Anatomy'. The terms were gathered from the Medical Subject Headings (MeSH) for translation to Tagalog language. MeSH served as the primary source and backbone of medical terms that were translated. Dictionaries from English-Tagalog/Pilipino/Filipino and glossaries were consulted in translating the terms. The priority translation tools are those that have been ranked by the experts. Informants such as medical doctors specializing in specific fields such as veterinarians, biologists and others, for instance, "mataderos", "hilots"... etc. and residents of Bulacan were likewise consulted. At the same time, experts' advice was sought regarding the ambiguity of terms. While thesaurus construction was a complex task, particularly the translation phase, still the project was able to attain some of its purposes. Out of the 51 MeSH terms gathered, 18 terms have definitions and 35 have Tagalog equivalents, the terms provided by the non-professional respondent that were not on the list amount to 4 terminologies with equivalent meanings in English in the dictionaries consulted. Only 52 terms were made as thesaurus entries and 8 for dictionary entries.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Anatomy; Filipino Language -- Medical Filipino